2016
DOI: 10.1111/ppc.12150
|View full text |Cite
|
Sign up to set email alerts
|

Cariprazine for the Treatment of Bipolar Disorder

Abstract: Cariprazine will be a promising addition in the treatment of patients with acute mania and schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Cariprazine is approved for the treatment of schizophrenia and acute manic or mixed episodes associated with bipolar I disorder (Agai-Csongor et al, 2012; Veselinovic et al, 2013; Findlay et al, 2017) It is a dopamine D2/D3 receptor partial agonist(McCormick et al, 2010; Kiss et al, 2012; Ellenbroek and Cesura, 2015) and in a mouse model of depression, it produced antidepressant-like activity (Duric et al, 2017). We tested if cariprazine, used in a dose previously reported in mice and equivalent to a typical human dose, has any effect on sterol levels in the brain and serum.…”
Section: Resultsmentioning
confidence: 99%
“…Cariprazine is approved for the treatment of schizophrenia and acute manic or mixed episodes associated with bipolar I disorder (Agai-Csongor et al, 2012; Veselinovic et al, 2013; Findlay et al, 2017) It is a dopamine D2/D3 receptor partial agonist(McCormick et al, 2010; Kiss et al, 2012; Ellenbroek and Cesura, 2015) and in a mouse model of depression, it produced antidepressant-like activity (Duric et al, 2017). We tested if cariprazine, used in a dose previously reported in mice and equivalent to a typical human dose, has any effect on sterol levels in the brain and serum.…”
Section: Resultsmentioning
confidence: 99%
“…The neuropharmacological profile of cariprazine is generally considered to be similar to aripiprazole, another atypical antipsychotic that is commonly used for the treatment of schizophrenia and bipolar disorder, except that cariprazine has a greater affinity and selectivity for D 3 vs. D 2 receptors ( Tadori et al, 2011 ; Ellenbroek and Cesura, 2015 ; Findlay et al, 2016 ; Stahl, 2016 ). Aripiprazole also has been shown to be effective as an adjunct treatment for major depressive disorder ( Bourin et al, 2009 ; Lenze et al, 2015 ; Zhou et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cariprazine, a novel, orally active antipsychotic agent that is a potent dopamine D 2 /D 3 receptor partial agonist with preferential binding to D 3 receptors, was recently approved by the U.S. Food and Drug Administration for the treatment of both schizophrenia and acute manic or mixed episodes associated with bipolar I disorder ( Ágai-Csongor et al, 2012 ; Veselinovic et al, 2013 ; Findlay et al, 2016 ). Among atypical antipsychotics, cariprazine displays the highest D 3 receptor binding affinity and D 3 vs. D 2 receptor selectivity (by approximately 6- to 8-fold) ( Kiss et al, 2010 ; McCormick et al, 2010 ; Ellenbroek and Cesura, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cariprazine, which has been authorized for use in the treatment of mania accompanying BD, is a partial D 2 /D 3 receptor agonist [332][333][334][335][336][337][338]. It appears to be a safe and effective medication for acute mania and mixed episodes in BD [339][340][341][342]. Some research data have indicated that both low and high doses of cariprazine are effective and well tolerated as a drug treatment for mania, depression, and psychosis [343][344][345].…”
Section: Cariprazinementioning
confidence: 99%